PENGARUH SELF EFFICACY DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI MOTIVASI (Studi Pada Kantor Pusat Dinas Bina Marga Provinsi Jawa Tengah) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examined the effect of Self Efficacy and Empowerment on Job Satisfaction with mediation Motivation. This study aims to provide empirical evidence that Self Efficacy effect on Motivation, provide empirical evidence that the effect on Motivation Empowerment, Self Efficacy effect on Job Satisfaction, Empowerment effect on Job Satisfaction and Motivation effect on Job Satisfaction. The population in this study were all employees of the central office of the Department of Highways Central Java province's status as a civil servant in the sample is determined by purposive sampling method ie method of sampling based on certain criteria. In this study sampled criteria are Civil Servants which is at least high school or equivalent qualified and have had work experience of at least 1 (one) year. This study is a survey research and data required in this study is primary data with the questionnaire as research instrument that is distributed directly to the respondents. The data processing used in the analysis include validity, reliability test, regression test, F test, t test and the coefficient of determination. Results of this study indicate that Self Efficacy and Empowerment positive and significant impact on employee Motivation Highways Agency Central Java Province, Self Efficacy and Empowerment positive and significant effect on Employee Job Satisfaction Employee Department of Highways Central Java Province, as well as the positive influence motivation and significant impact on Employee Job Satisfaction Highways Agency Central Java Province. Keywords: Self Efficacy, Empowerment, Motivation, Job Satisfaction